Media Jihad: Interpretation of Palestinian Resistance Through Semiotic Studies - Sa’idul Arfan; Fahrurrozi; Nikmatillah; Sobihatun Nur Abdul Salam (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study discusses the concept of “Media Jihad” and its role in interpreting the resistance of the Palestinian people. By examining various forms of media, such as social media posts, news articles, and visual images, this research aims to reveal the forms of Palestinian resistance through semiotic analysis. Through the lens of semiotics, the study explores how media representations shape public perceptions and contribute to the narrative of the Palestinian struggle. This research employs a qualitative descriptive method. The data collected includes sentences, images, hashtags, and symbols from social media posts, news articles, and visual images. The data collection method used is non-participatory observation, where the researcher observes and records sentences, images, hashtags, and symbols in these various media and then correlates them with their context based on semiotic theory. Additionally, the researcher conducts interviews with community leaders and experts in interpretation to gain deeper perspectives. After collecting the data, the researcher processes it through reduction, classification, verification, and tabulation based on its type, then performs interpretation and concludes the findings. The research results show that the resistance of the Palestinian people manifests in the following forms, namely 1) expressions of condemnation of Israel; 2) visual images such as pamphlets, flags, cartoons, and documentary films; 3) supportive, struggle, and condemnation hashtags; and 4) symbols like watermelons, kufiya or smagh, and keys. This research contributes to a deeper understanding of the role of media in conflict zones and the importance of semiotics in interpreting resistance movements.